Characterization of polymorphic microsatellite loci in the western rock lobster (Panulirus cygnus) - Groth, David; Lim, F.; de Lestang, S.; Beale, N.; Melville-Smith, R. (Springer, 2009)
Nine microsatellite loci were identified in the western rock lobster (Panulirus cygnus) using two different methods. The first method involved the screening of a small, fragment, partial genomic library with a radioactive (CA) 6 probe. The second method, was based upon an enrichment method and used biotinylated, tetranucleotide microsatellite oligonucleotide capture probes. The nine loci described are all very polymorphic, with 11 to 34 alleles observed for each locus and heterozygosities ranging from 0.58 to 0.86. These microsatellite loci will be useful in analysing both the population structure and the mating systems used by this species and will add important information for the management of the wild stocks of this economically important species. © Springer Science+Business Media B.V. 2009.